BIROKRASI DESA DALAM PERSPEKTIF MANAJEMEN SUMBER DAYA MANUSIA PERANGKAT DESA (Studi Kasus di Kabupaten Lebak Provinsi Banten) - RUSITO RUSITO (LPPM STIA Banten, 2017)
With the decentralization pattern to the village, professional village government is needed. However, the conditions that occur are still many village governments whose personnel are less professional because the village government is still cultured long. For that professional village bureaucracy in village government organizations to be one solution. The purpose of this paper is to gain an understanding of who the professional village bureaucracy and the stage of bureaucratic management of the village with a case study in Lebak regency of Banten Province. The framework used is Janet V Denhart et al (2007: 121) thought, Miftah Thoha (2010: 154), Paul Hersey, et al (2008: 230) and some Human Resources Management experts. The conclusion of this paper is that the development of the organization and management of the village government passes through the village government stage of the village bureaucracy as the foundation in the further development of the organization and management of the village government. To realize a professional bureaucracy the village government needs to be managed with human resource management.